Alat Make Up Sebagai Objek Dalam Karya Seni Lukis - Hanifa Hafshah; Ferdian Ondira Asa (Jurnal Riset Rumpun Seni, Desain dan Media, 2023)
The purpose of this work is to convey a message by visualizing negative behavior in the form of women's insecurity with the object of make-up tools that are metaphorized in contemporary painting. The method of creating works using an art consortium through five stages, namely, the preparation stage (observation and exploration), the elaboration stage (searching and collecting references), the synthesis stage (application of main ideas), the realization of concepts (making works), and the completion stage (artist report and final work exhibition). So that the realization of ten works that the author made with the theme of feelings of insecurity, the resulting works are 9 works with a size of 120x100 cm and 1 work with a size of 150x100 cm, with the titles lipatan, keinginan, paksaan, apakah aku sudah berbeda?, logika, kenyataan, pengangggu, penyamaran, mencoba, dan obsesi.